KEANEKARAGAMAN JENIS BURUNG PADA BERBAGAI TIPE PEMANFAATAN LAHAN DI KAWASAN MUARA KALI LAMONG, PERBATASAN SURABAYA – GRESIK - Hening Swastikaningrum; Sucipto Hariyanto; Bambang Irawan (The East Java Biological Society, 2012)
The object of this study was to determined the bird species diversity around the estuary region of Kali Lamong located in between Surabaya and Gresik, East Java. Observation was taken three kilometers far, started from Galang Island in Kali Lamong estuary to upstream side of the river. Twelve stations were made along the river as representative type of five land use. Station I and IV represented settlement area. Station II, III, and VIII represented industrial sites, station V and VI represented lawn, and station VII, IX, and X represented aquaculture. Each stations had 20 meter (bulls eye diameter) range or equivalent with 1.256 m2. Every bird in the area was recorded and analyzed by Shannon- Wiener diverity index. The results of this study shown aquaculture area has the highest diversity index (3,19). Followed by lawn (2,52), industrial site (2,39), mangrove forest (2,06), and settlement area (1,67).